2012
DOI: 10.1103/physreva.85.012325
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-spin coherence transfer in linear Ising spin chains and beyond: Numerically optimized pulses and experiments

Abstract: FIG. 4. A linear four-spin chain has only direct couplings J 12 , J 23 , and J 34 between neighboring spins. We split the corresponding four-spin chain control problem into two subproblems for three-spin chains.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 71 publications
(131 reference statements)
0
37
0
Order By: Relevance
“…Significant progress has been made in understanding of how to optimally control coupled spin systems with more than two spins [65,71,86,87,[313][314][315][356][357][358][359][360][361][362][363][364][365][366][367][368][369][370][371][372][373][374]. Recent advances include robust broadband and band-selective pulses in NMR and ESR.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made in understanding of how to optimally control coupled spin systems with more than two spins [65,71,86,87,[313][314][315][356][357][358][359][360][361][362][363][364][365][366][367][368][369][370][371][372][373][374]. Recent advances include robust broadband and band-selective pulses in NMR and ESR.…”
Section: State Of the Artmentioning
confidence: 99%
“…State preparation protocols include transport of atoms [436] and ions [437,438] as well as transport in a spin chain [86,356,359,363,369,439,440], photon storage [441], preparation of squeezed states [442], cluster-states [443], non-classical states in a cavity [444] or in spin chains [364,365], as well as preparation of a quantum register [122] and many-body entangled states [123,445,446] -to name just a few.…”
Section: State Of the Artmentioning
confidence: 99%
“…Another option could be to consider the dynamics of a linear chain of three coupled spins subjected to radio-frequency magnetic fields [20,21,22]. Previous studies have shown that the optimal controlled trajectories of this system are given by solutions of Euler equations [23,24]. Work is in progress on these different points.…”
Section: Discussionmentioning
confidence: 99%
“…We search for a solution ǫ 0 of the above equation in the form (24) with u a differentiable function of λ, µ, with u(0, 0) = 0. Note that ǫ 0 (u, λ, µ) is smooth at (u, λ, µ) = (0, 0, 0).…”
Section: Computation Of ǫmentioning
confidence: 99%
“…However, the same transfer (and amplification) can be obtained relying on the evolution driven by spin-spin couplings; this alternative strategy can in principle lead to a transfer speed-up [94][95][96] thanks to optimal control techniques. More generally, QST driven by interactions between spins in the chain, without the requirement of single-spin control, is a more powerful paradigm that can in principle be implemented in larger spin chains.…”
Section: Simulations With Liquid-state Nmrmentioning
confidence: 99%